Pityriasis folliculorum colocalized with vitiligo: An example of immunocompromised cutaneous district - Ayse Tulin Mansur (Our Dermatology Online, 2018)
The concept of immunocompromised cutaneous district suggests that different types of skin injuries can render the affected areas vulnerable to subsequent opportunistic infections, tumors, and immune reactions. Herein a 44-year-old woman with facial vitiligo associated with pityriasis folliculorum, a type of demodicosis, is reported. The right cheek with a large patch of vitiligo showed clinical, dermoscopic and microscopic evidents of demodicosis, while the other facial areas without vitiligo were devoid of Demodex mites. This case is another example of immunocompromised cutaneous district, probably developed due to immunologic alterations and increased ultraviolet light exposure caused by vitiliginous skin.